The Research on Consumer Attitudes Towards Influencers and Their Collaboration With Brands in Bulgaria - Mikova, Radoslava (Media and Language, 2024)
The research aims to examine consumer attitudes towards influencers and their collaborations with brands in Bulgaria. It was conducted online during the period December 2020 – January 2021. A total of 304 respondents completed a questionnaire with 18 closed and open-ended questions. The primary objective is to determine whether there is a presence of pseudo-influence in Bulgaria, driven purely by profitability, or if there is an evolving influencer culture. Additionally, the study seeks to answer whether Bulgaria genuinely has influencers or if it follows a Western model of product and service consumption behavior.
Keywords: brand; branding; influencers; social media